Case Series: Evidence of Borderzone Ischemia in Critically-Ill COVID-19 Patients Who “Do Not Wake Up” - Pirau, Letitia; Ottenhoff, Lauren; Williamson, Craig A.; Ahmad, Shahid N.; Wabl, Rafael; Nguyen, Andrew; Faiver, Laura; Rajajee, Venkatakrishna (Frontiers in Neurology, 2020)
We describe the clinical course, radiological findings and outcome of two patients with the novel 2019 coronavirus disease (COVID-19) who remained comatose for prolonged duration following discontinuation of all sedation. A 59-year-old man and a 53-year-old man, both with history of hypertension and neurologically intact on admission, developed worsening COVID-19 associated acute respiratory distress syndrome (ARDS). Both required benzodiazepine, opioid, neuromuscular blockade, therapeutic anticoagulation and vasopressor infusions in addition to renal replacement therapy. Echocardiography demonstrated normal chamber size and systolic function in both cases. Both patients demonstrated only trace flexion to pain 7-10 days following discontinuation of all sedation. Magnetic Resonance Imaging (MRI) on both patients demonstrated multifocal Diffusion Weighted Imaging (DWI) lesions with apparent diffusion coefficient (ADC) correlate in bilateral middle/ anterior cerebral artery (MCA-ACA) borderzones, with no large-vessel occlusion or severe stenosis. In both patients, continuous electroencephalography demonstrated no seizures. Both patients demonstrated significant neurological improvement between 45-60 days following admission, and were able to speak short sentences, with hemiparesis, at the time of discharge, with further improvement anticipated. Neither patient had any documented period of sustained hypotension (mean arterial pressure <60mmHg) or hypoxia (SpO2<90%). We conclude that critically-ill COVID-19 patients with prolonged coma following sedation discontinuation may demonstrate imaging features of ischemic injury in borderzone regions despite the absence of documented sustained hypotension or hypoxia. However, substantial neurological improvement is possible despite these findings.